Penerapan Akuntansi Manajemen dalam Usaha Mikro Kecil dan Menengah (UMKM) : Aku Cendol Kamu Salatiga - Paskah Ika Nugroho; Joshelynar Gwyneth Takaliwuhang (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
This study looks at how the application of management accounting functions and factors. Aku Cendol Kamu Salatiga the object of research. Primary and secondary data are used in this study. This study uses qualitative methods using interactive analysis. Data obtained directly from the owner of Aku Cendol Kamu Salatiga and data analysis in the field so that it is more representative. Data collection techniques are used to collect data that can be seen from its use through observation and so on. Data that must provide information based on supporting facts, including by conducting (1) Interviews, (2) Observations. Interviews were submitted to the owner of the research object in the form of unstructured questions. Observations are made directly so that relevant results are obtained, and can also be used as a reference. The results of observations and interviews are presented in tabular form with a clear presentation of the object of research in applying the functions of implementing management accounting namely planning, organizing, directing, controlling, and decision making.